Perspectives and preferences of domestic violence survivors regarding digital platform and AI chatbot for help-seeking: A qualitative study - Vivian Hui; Lidan Tian; Xinyu Feng; Qiqi Chen; Arkers Kwan Ching Wong; Tina L. Bloom (PLoS ONE, 2026)
Background Domestic violence (DV) is a pervasive public health issue with profound physical, psychological, and social consequences. Help-seeking, particularly access to advocacy interventions, plays a pivotal role in promoting resilience and mental health well-being among DV survivors. Digital platforms and AI chatbots are emerging as promising tools for information and support. However, limited research has explored the views and needs of DV survivors regarding these technologies, impeding the development of culturally sensitive interventions for help-seeking. Objective This study aimed to investigate the perspectives and preferences of digital platform and AI chatbot among people with DV experience in Hong Kong, which could offer valuable insights to inform the design of tailored technological solutions for help-seeking. Methods Semi-structured qualitative interviews were conducted with 36 individuals who had DV experience over the past decade. Interviewees were recruited from DV-specific non-governmental organizations (NGOs) in the community using convenience and snowball sampling. Interviews took place either in-person or via videoconference between April 2023 and August 2024. Data were analyzed using reflexive thematic analysis, combining deductive and inductive approaches. Three trained coders identified themes and sub-themes through an iterative and collaborative process. Results We identified three key themes regarding the recommended features of digital platforms: functions, content, and format. Regarding content, participants valued evidence-based information, step-by-step guidance, and survivor narratives. For format, participants valued procedural visualization, engaging multimedia, calming visual design, and clear text layout. Participants emphasized the potential of AI chatbots, highlighting benefits such as enhanced accessibility, efficient information filtering, and providing nonjudgmental feedback. However, concerns were raised about chatbots’ limitations, particularly in empathy, personalization, and information accuracy. Conclusions DV survivors preferred digital platforms that prioritize safety, accessibility, and emotional support. Our study highlights the role of AI as a complementary tool to human support and calls for participatory approaches to facilitate designing effective interventions to reach their full potential.